2015
DOI: 10.1287/mnsc.2014.1987
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation on the Appointments of Supply Chain and Operations Management Executives

Abstract: T his paper provides empirical evidence on the performance effects and choice of appointments of supply chain and operations management executives (SCOMEs). The analysis is based on a sample of 681 SCOME appointments that were publicly announced during the 2000-2011 period. We find that the stock market reaction is positive on the day of the announcement. Categorizing the SCOME appointments as new or old and insider or outsider, we find that the market reaction for newly created SCOME positions is positive. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 55 publications
4
118
0
Order By: Relevance
“…The small share of women in SCM is in line with recent studies that found SCM to be a male‐dominated profession (Hendricks et al. ; O'Marah ). Of the executives in the sample, 86.6% work in Germany, 8.8% in Switzerland, and 4.6% in Austria, a distribution that is proportional to these countries’ populations.…”
Section: Datasupporting
confidence: 85%
See 2 more Smart Citations
“…The small share of women in SCM is in line with recent studies that found SCM to be a male‐dominated profession (Hendricks et al. ; O'Marah ). Of the executives in the sample, 86.6% work in Germany, 8.8% in Switzerland, and 4.6% in Austria, a distribution that is proportional to these countries’ populations.…”
Section: Datasupporting
confidence: 85%
“…This definition complies with the description by Dalton () and is also applicable to the labels used by Hendricks et al. (). In line with those authors and the CSCMP's definition (), we consider “CSCOs,” SCM “(executive/senior) vice presidents,” “directors,” and “heads” (and the equivalents “principals,” “leaders,” and “Leiter”) to be SCEs in this study.…”
Section: Literature Review and Development Of Research Questionsmentioning
confidence: 64%
See 1 more Smart Citation
“…Several studies have estimated abnormal returns using the four-factor model [30] [33]. The fourfactor model posits a linear relationship between the stock return and four factors over a given time period (Formula 1): (1) where R it is the return of stock i on day t, α i is the intercept of the relationship for stock i, R ft is the riskfree return on day t, R mt is the return on the market portfolio on day t, SMB t is the small minus big size portfolio return on day t, HML t is the high minus low book-to-market portfolio return on day t, UMD t is the past-one-year winners-minus-losers stock portfolio return on day t, and ε it is the error term [14]. Abnormal returns are defined as the difference between the actual return and an estimated expected return in the absence of an event.…”
Section: Methodsmentioning
confidence: 99%
“…Bertrand and Schoar (2003) present the seminal econometric analysis of upper level manager effects on firm policy and performance. Recent analyses on game developers (Mollick, 2012), supervisors (Lazear et al, 2015), store managers (Siebert and Zubanov, 2010), operations managers (Hendricks et al, 2014) and car sales managers (Owen et al, 2015) document similar evidence for managers at lower organizational levels. 2 For education, a positive correlation is usually found (Chevalier andEllison, 1999, Goldfarb andXiao, 2011), with the exception of Mair (2005).…”
mentioning
confidence: 92%